1988
DOI: 10.1002/1097-0142(19881101)62:9<1946::aid-cncr2820620913>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Histogenesis of renal cell carcinoma and renal oncocytoma: An immunohistochemical study

Abstract: The histogenesis of renal cell carcinoma and oncocytoma is controversial. We compared immunohistochemical profiles of normal kidney, nine carcinomas, and six oncocytomas. Carcinomas and oncocytomas expressed the following antigens respectively: proximal tubule--Uro 3 (56 & 67%), alpha-1-antitrypsin (89 & 50%); proximal and distal tubule--Uro 10 (67 & 83%); distal tubule--B2-microglobulin (100 & 100%); distal/medullary tubule--epithelial membrane antigen (89 & 83%), neuron-specific enolase (78 & 100%), glandula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0
1

Year Published

1990
1990
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 37 publications
3
26
0
1
Order By: Relevance
“…Those observations led to the conclusion that TCC epithelial cells show aberrant renal tubular differentiation. This coexistence of proximal and distal tubules characteristics has been reported in several renal tumors [3,4,8,15] indicating that aberrant tubular differentiation may be a common occurrence in renal neoplasms regardless of their nephron origin. All reported cases present a homogeneous macroscopic and cytoarchitectural appearance: they have a spongy "bubble-wrap" appearance due to small to interme- diate (and occasionally large) cystic structures dispersed within a thin fibrotic stroma.…”
Section: Discussionsupporting
confidence: 70%
“…Those observations led to the conclusion that TCC epithelial cells show aberrant renal tubular differentiation. This coexistence of proximal and distal tubules characteristics has been reported in several renal tumors [3,4,8,15] indicating that aberrant tubular differentiation may be a common occurrence in renal neoplasms regardless of their nephron origin. All reported cases present a homogeneous macroscopic and cytoarchitectural appearance: they have a spongy "bubble-wrap" appearance due to small to interme- diate (and occasionally large) cystic structures dispersed within a thin fibrotic stroma.…”
Section: Discussionsupporting
confidence: 70%
“…On the other hand, distal tubulus epithelial cells represent the precursor cells of oncocytomas. 16 Thus, PTEN expression is nearly lost during carcinogenesis of ccRCCs, suggesting an important role in tumorigenesis. In contrast, loss of PTEN during pathogenesis of oncocytomas was not observed, since PTEN expression is less intense in both oncocytomas and their precursor (distal tubulus) epithelial cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is widely believed that VHL associated renal tumors originate from the proximal nephron [1,107], it has been shown that CC-RCCs can express markers of both, the distal and the proximal nephron [110][111][112][113], implying a multipotential capacity of neoplastic renal cells to synthesize antigens that can be associated with different tubular segments and different stages of nephrogenesis. More recently Maxwell's group reported that in kidneys from VHL patients "early" multicellular lesions appeared to be more frequently derived from Tamm-Horsfall protein (THP) expressing tubular segments than from the proximal tubule.…”
Section: Conditional Inactivation Of Pvhl In the Kidney: Towards The mentioning
confidence: 99%